α-Synuclein Mutation Inhibits Endocytosis at Mammalian Central Nerve Terminals - Xu, Jianhua (J Neurosci, 2016)
α-Synuclein (α-syn) missense and multiplication mutations have been suggested to cause neurodegenerative diseases, including Parkinson's disease (PD) and dementia with Lewy bodies. Before causing the progressive neuronal loss, α-syn mutations impair exocytosis, which may contribute to eventual neurodegeneration. To understand how α-syn mutations impair exocytosis, we developed a mouse model that selectively expressed PD-related human α-syn A53T (h-α-syn(A53T)) mutation at the calyx of Held terminals, where release mechanisms can be dissected with a patch-clamping technique. With capacitance measurement of endocytosis, we reported that h-α-syn(A53T), either expressed transgenically or dialyzed in the short term in calyces, inhibited two of the most common forms of endocytosis, the slow and rapid vesicle endocytosis at mammalian central synapses. The expression of h-α-syn(A53T) in calyces also inhibited vesicle replenishment to the readily releasable pool. These findings may help to understand how α-syn mutations impair neurotransmission before neurodegeneration. SIGNIFICANCE STATEMENT α-Synuclein (α-syn) missense or multiplication mutations may cause neurodegenerative diseases, such as Parkinson's disease and dementia with Lewy bodies. The initial impact of α-syn mutations before neuronal loss is impairment of exocytosis, which may contribute to eventual neurodegeneration. The mechanism underlying impairment of exocytosis is poorly understood. Here we report that an α-syn mutant, the human α-syn A53T, inhibited two of the most commonly observed forms of endocytosis, slow and rapid endocytosis, at a mammalian central synapse. We also found that α-syn A53T inhibited vesicle replenishment to the readily releasable pool. These results may contribute to accounting for the widely observed early synaptic impairment caused by α-syn mutations in the progression toward neurodegeneration.